Encyclopedia of Life Sciences 2020
DOI: 10.1002/9780470015902.a0000601.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes: Irreversible Inhibition

Abstract: Many drugs that are in clinical use work by irreversibly inhibiting specific enzymes, either in the individual being treated or in an invading organism. Enzyme inhibitors are also of value for understanding the behaviour of individual enzymes and metabolic systems. Recovery from irreversible inhibition requires the synthesis of new enzyme. Although those irreversible inhibitors that react with specific groups in the enzyme protein generally inhibit more than one enzyme, those that initially form a noncovalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…[19,20] Due to the fast reaction kinetics of CrabTag inhibition, a key assumption to our model was a pseudo-steady state hypothesis on the concentration of fluorescent linker 11. [21] Using a non-linear regression as our statistical model, we simultaneously solved the system of differential rate law equations and estimated the second-order kinetic rate constant parameters from the model (Figures S12-14, Tables S3-S6). This experiment revealed that a mechanistic approach could be used to describe and monitor the stepwise assembly of an atomically precise multi-protein scaffold over time.…”
Section: Resultsmentioning
confidence: 99%
“…[19,20] Due to the fast reaction kinetics of CrabTag inhibition, a key assumption to our model was a pseudo-steady state hypothesis on the concentration of fluorescent linker 11. [21] Using a non-linear regression as our statistical model, we simultaneously solved the system of differential rate law equations and estimated the second-order kinetic rate constant parameters from the model (Figures S12-14, Tables S3-S6). This experiment revealed that a mechanistic approach could be used to describe and monitor the stepwise assembly of an atomically precise multi-protein scaffold over time.…”
Section: Resultsmentioning
confidence: 99%
“…They can be classified into two main types: reversible inhibitors and irreversible inhibitors. They can have therapeutic applications in the treatment of several diseases [60].…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 99%
“…However, the amount of any specific enzyme protein present does not necessarily correspond with its activity. The rates of enzyme synthesis and degradation vary widely, and the amount of an enzyme within the cell is not constant and can vary as a result in changes in metabolic conditions [ 64 , 65 ].…”
Section: Approximating the Activity Within The Cellmentioning
confidence: 99%